Inabah Leadership System in Improving the Role of Service for the Victims of Narcotics, Psychotropic and Addictive Substances through the Tarekat Qodiriyah-Naqsabandiyah - Wawan Wawan (International Journal of Nusantara Islam, 2019)
This research is to find out how the leadership system, strategy, process, results of constraints and support as well as hypothetical concepts that exist in Inabah. The theory in this study refers to Reconstructionism theory. The method used is descriptive analytical with a qualitative approach. The research techniques using observation techniques, interviews and documentation as a data collection tool. The results of this study: first, the leadership system developed at Inabah indicated the transformational leadership model/pattern. Second, the strategy or approach used by Inabah leaders towards drug victims through the Qodiriyah Naqsabandiyah Order (Tarekat Qadiriyah-Naqsabandiyah [TQN]) with a religious non-medical approach. Third, the process developed at Inabah with therapy underwent three main practices with the TQN method which was carried out continuously and continuously through activities such as purification (thaharah ), bathing, ablution, prayer, and dhikr. Fourth, the results developed can be said to be successful if the santri have carried out all education in the Suryalaya, Fifth, Islamic boarding schools. Support and support in Inabah is: Serba Bakti Foundation, Forrnal and Non-formal educational institutions, Koperasi Hidmat, Inabah Youth Cottage, Mrs. Belia, Young Generation Suryalaya, Radio Inayah, Sinthoris Magazine. Sixth, the hypothetical concept of the leadership of Abah Anom refers to the purpose of the TQN which is the same as the goal of Islam itself, which is to guide people to get the blessing of Allah, prosper in the World and happy in the Hereafter.